At the frontlines of development : reflections from the World Bank - Gill, Indermit Singh, 1961-; Pugatch, Todd.; World Bank. (Washington, D.C. : World Bank, 2005)
This book is part of a larger effort undertaken by the World Bank to understand the development experience of the 1990s. This volume considers the operational implications of the decade for the World Bank as an institution.
Includes bibliographical references and index.
oif 26/08/15
Loan
Keywords: World Bank; Economic development; International finance